Obesity - Risky Phenomenon of our Time - Mohamed, Ashour S A (2008)
A greater proportion of children and adolescents are overweight than ever before, this has sounded a public are much more likely to end up obese when they are adults. People come in all different shapes and sizes, and the best weight for your so one that is right for your in dividual body type and size. It can be unhealthy to be too thin if we are eating less food than your body needs. eating enough food is like putting gas in your car-if you run out countries with respect to extra weight and obesity. The dramatic increase in the prevalence of childhood obesity within the last decade has changed the view on childhood obesity and the condition is now seen as one of the top 10 global health problems. The problem that is thought to occur with increased frequency among obese people is binge eating as the frequent and intake of an objectively large amount of food with an associated sense of control over eating.